Students’ Attitudes toward Online Formative Assessments in English Language Learning in SMA Negeri 1 Kembang - Mifro Datun Anisa (Universitas PGRI Semarang, 2021)
Online learning is part of all distance education, always providing access to education that is at least more flexible in time and space education. As it is known assessment becomes one of the learning aspects that change in online learning, including formative assessment that must be done online too. In this case, it is important to know how students' attitudes towards online formative assessment in teaching and learning are. By using a mixed-method research design, the authors collect data with the help of several instruments, namely observation, MSLQ, Closed-questionnaire, and semi-structured interviews. In this study, 50 students were included as the research sample. Final data shows that students have high motivation toward online formative assessment. In the implementation of online formative assessment, students also experience several obstacles such as internet connection, lack of supporting devices, etc.